Implementation of Management Functions in the Development of Teacher Resources in Islamic Education Institutions - Alifiyah, Nur; Maulidi, Akrom; Uyuni, Yuyun R.; Bachtiar, Machdum (Formosa Journal of Science and Technology, 2024)
The research method used in this research is library research research where the reference sources used come from journals, books and so on. The results of this research show that the implementation of management functions in developing teacher resources in Islamic educational institutions is as follows: (1) planning development programs such as education and training (training) for teachers; (2) make a schedule for teacher development (training) programs on a regular basis; (3) make a budget plan for the teacher training development program; (4) determine procedures or rules for training programs that can be used as evaluation material. (6) Grouping teachers' duties and responsibilities; (7) Grouping teaching staff according to needs to carry out training. Development in educational institutions can be carried out through several programs such as training and education (diklat), workshops and holding subject teacher deliberations (MGMP) , mentoring and coaching and independent learning. Supervision is a series of actions carried out to find out the extent to which the teacher development program is running well in accordance with predetermined plans.